Environmental Efficiency of Agriculture in Visegrád Group Countries vs. the EU and the World - Arkadiusz Sadowski; Natalia Genstwa-Namysł; Jagoda Zmyślona; Luboš Smutka (Agriculture)
The production of foodstuffs for an ever-increasing population is the basic, irreducible and unalienable function of agriculture. It involves environmental impacts, including greenhouse gas emissions. This is what makes it so important to examine the levels of environmental efficiency of agriculture. As countries differ in their emission levels, it is reasonable to look for what determines them. Hence, the purpose of this study was to identify the changes in the environmental efficiency of agriculture in Visegrád Group countries and worldwide in 1961–2020. These countries share a similar economic history and demonstrate comparable environmental and geographic conditions, making it possible to pinpoint the factors responsible for how the parameters covered by the study change over time. The research used data from the FAOSTAT database. Environmental efficiency of agriculture was defined as the relationship between production volumes in kilocalories and emissions. Initially, this parameter deteriorated in the Visegrád countries, but since the late 1970s it has improved, first linked to the crisis of the socialist economy and its collapse (including a drastic decline in livestock production) and then to the implementation of CAP instruments.